Ginástica rítmica no Espírito Santo: uma história contada pelos seus precursores - Dias, Franciny dos Santos (2019)
This study addresses the trajectory of Rhythmic Gymnastics (RG) in Espírito Santo. For a better understanding of this sport's history in the State, it presents a brief Brazilian RG history, which was marked by the accomplishment of the Technical-Pedagogical Improvement Courses, in the 1950s, in São Paulo State (CBG, 1984; CRAUSE, 1985; ALONSO, 2011). Through these courses, the RG, previously called Modern Gymnastics (MG), was promoted in Brazil by the Austrian teacher Margareth Frölich, in 1953. In the same period, Hungarian teacher Ilona Peuker was in the country and became the main disseminator of this sport (CRAUSE, 1985). In Espírito Santo, the beginning of RG had the contribution of teacher Geny Curcio, in the city of Cachoeiro de Itapemirim, in 1953, after her participation in courses taught by European teachers. In the work developted, with her group of band leaders, the teacher improved her knowledge of RG. Since then, RG of Espírito Santo has undergone a continuous development process, becoming a national reference (SARTÓRIO, 2011). Despite the long history of the Espírito Santo RG, few studies have reported the historical aspects of this sport. Therefore, the aim of this study was to bring the narratives of RG stories in the State and analyze them, through the reports of the 20 collaborators who contributed to the research, in order to understand how the process of consolidation of the RG ocurred in the State. To reach the study goal, oral history was adopted as a methodology, making use of the thematic interview, which strives for the individual's participation in the study theme (ALBERTI, 2005). The analysis of the research was carried out using the comparative method, which aims to investigate things, facts and explanations, considering their similarities and differences (FACHIN, 2001). Thus, the selected collaborators were separated into five groups: pioneers, gymnasts, coaches, directors and a multidisciplinary team. This research envisioned that the success of the gymnastics discipline is associated with a series of factors, such as the influence of European teachers, the work of pioneer teachers, the support of Espírito Santo universities, the inclusion of RG in the school environment, the creation of a regulated Federation, the laws and incentive programs stipulated by government, the commitment of the coaches, the family support, the encouragement of a multidisciplinary team and, primally, the dedication of the gymnasts.